ESTUDO DA ATIVIDADE DE RELAÇÕES PÚBLICAS EM INSTITUIÇÕES DE ENSINO SUPERIOR BRASILEIRAS - Simas, Rutelena de Lacerda (2004)
This is a definite work on Public Relations activities on Brazilian Graduate Institutes (BGI). It embraces themes on Social Communication and Public Relations which establishes the theoretical reference of such study. This study was taken along with 35 respondents acting at the Social Communication and/or at the Head Chair of the Institutions already mentioned. The data reached were analyzed as to allow a better comprehension on Public Relation practices of such institutions.